Ultrasonography of the gastrointestinal tract of toco toucans (Ramphastos toco) - da Silva, Jeana Pereira [UNESP]; Rahal, Sheila Canevese [UNESP]; Castiglioni, Maria Cristina Reis [UNESP]; Rolim, Luna Scarpari [UNESP]; Lima, Whítara Ferreira [UNESP]; Schimming, Bruno Cesar; Moresco, Anneke; Mamprim, Maria Jaqueline [UNESP] (Wiley, 2021)
Baseline data for wall thickness in healthy toucans can be used to diagnose disease in sick individuals. This study aimed to evaluate the use of ultrasonography for the examination of the gastrointestinal tract of healthy toco toucans (Ramphastos toco). Ten non-anaesthetized healthy adult toco toucans were evaluated. Food was withheld for 3 h prior to the ultrasound examination. Longitudinal and transverse images of the gastrointestinal tract were obtained using ventromedian cranial and ventromedian caudal approaches to evaluate the morphology and stratification. The wall thickness of the sections was measured: proventriculus and ventriculus, duodenum, jejunum/ileum, and cloaca. Additionally, the thickness of the mucosal layer of the duodenum and jejunum/ileum was also measured. Subsequently, the ratios of the duodenal wall thickness to the duodenal mucosa layer and the total wall thickness of the jejunum/ileum to the jejunum/ileum layer mucosa were stablished. The wall thickness of the proventriculus was significantly higher than the wall thickness of ventriculus. The wall thickness of the duodenum was significantly higher than the wall thickness of jejunum/ileum. The mean ratios of the duodenal wall thickness to the duodenal mucosa layer and the wall thickness of the jejunum/ileum to the jejunum/ileum layer were 83.15% and 80.07%, respectively. In conclusion, it was possible to assess the stomach and intestines using ultrasound examination in healthy toco toucans, due to their medium body size and no interference by surrounding air sacs.
Keywords: bird; duodenum; ileum; imaging study; jejunum; stomach